The safety and efficacy of hypothermia combining mechanical thrombectomy or thrombolysis in the treatment of ischemic stroke: A systematic meta-analysis (Clinics, 2023)
Background: Stroke is a major global public health problem, affecting 13.7 million people worldwide. Previous studies have found a neuroprotective effect of hypothermia therapy and the efficacy and safety of combined hypothermia and mechanical thrombectomy or thrombolysis in the treatment of ischemic stroke have also attracted attention.Objective: In the present research, the authors conducted a meta-analysis to comprehensively assess the safety and efficacy of hypothermia combining mechanical thrombectomy or thrombolysis in the treatment of ischemic stroke.Methods: Articles published from January 2001 to May 2022 were searched from Google Scholar, Baidu Scholar and PubMed to evaluate the clinical significance of hypothermia treatment in ischemic stroke. Complications, short-term mortality, and the modified Rankin Scale (mRS) in the full text was extracted.Results: 89 publications were selected and 9 among them were included in this study with sample size of 643. All selected studies are in accordance with the inclusion criteria. Forest plot of clinical characteristics was as follows: complications (RR = 1.132, 95% CI 0.942‒1.361, p = 0.186, I2 = 37.2%), mortality within 3 months (RR = 1.076, 95% CI 0.694‒1.669, p = 0.744, I2 = 0.00%), mRS ≤ 1 at 3 months (RR = 1.138, 95% CI 0.829‒1.563, p = 0.423, I2 = 26.0%), mRS ≤ 2 at 3 months (RR = 1.672, 95% CI 1.236‒2.263, p = 0.001, I2=49.6%) and mRS ≤ 3 at 3 months (RR = 1.518, 95% CI 1.128‒2.043, p = 0.006, I2 = 0.00%). The funnel plot suggested that there was no significant publication bias in the meta-analysis on complications, mortality within 3 months, mRS ≤ 1 at 3 months and mRS ≤ 2 at 3 months.Conclusion: In summary, the results showed that hypothermia treatment was correlated with mRS ≤ 2 at 3 months, but not linked with complications and mortality within 3 months.